Evidence for a highly conserved, immunoreactive lipid in Mycobacterium tuberculosis - Makonkawkeyoon S. (2014)
A survey of the fractionated lipids of Mycobacterium tuberculosis H37Rv was conducted using rabbit antiserum raised to homologous and heterologous mycobacteria. One minor, highly apolar lipid was resolved by Florisil column chromatography, which reacted preferentially to anti-M. tuberculosis H37Rv rabbit antibodies. Other chromatographic properties, i.e., thin-layer chromatographic mobility and staining properties, suggested an analog of the phenolic glycolipid of Mycobacterium leprae. Preliminary results in the application of the glycolipid to tuberculous populations in northeast Thailand suggest a usefulness in screening for tuberculosis.